Revascularization of chronic occluded celiac artery for gastroduodenal coil embolization in massive upper gastrointestinal bleed - Esther H. Shim, MD; Ryan Lydon, MD; Stephanie S. Hyon, MD; Robert J. Plummer, MD; Thomas Y. Lee, MD; Hal Ginsberg, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Upper gastrointestinal bleeding is a serious condition often linked to peptic ulcer disease, contributing to significant morbidity and mortality. A 78-year-old male presented with upper gastrointestinal bleeding that required blood product transfusions despite multiple endoscopic interventions. Although embolization or surgical ligation of the gastroduodenal artery was considered, angiography revealed celiac trunk occlusion, which would increase the risk of hepatic ischemia. Recanalization and stenting of the celiac trunk was performed, facilitating successful embolization of the gastroduodenal artery. This case illustrates the importance of considering anatomical variations and patient risk factors for visceral arterial occlusions, reducing morbidity and mortality.